Sustainable cultivated landscapes in Germany: Comparison of 27 practical measures for more sustainability and their effectiveness - Stefan Möckel; Marieke Baaken; Bartosz Bartkowski; Michael Beckmann; Michael Strauch; Jessica Stubenrauch; Martin Volk; Felix Witing; André Wolf (Helmholtz-Zentrum für Umweltforschung (UFZ), 2024)
With months of drought, hot summers and flooding, global warming has also become increasingly apparent in Germany over recent years. The Climate Protection Act, which was amended in 2021, therefore aims to achieve climate neutrality by 2045. At the same time, a favourable conservation status for habitats, species and water bodies are still the exception in cultivated landscapes, in spite of obligations under European law to achieve this. In this article, we estimate the potential impacts of various landscape designs and integrated landuse measures in terms of climate change mitigation and adaptation, favourable conservation status as well as long-term food security and profitable land use. Based on these impact assessments, we then identify priority measures to be taken. The comparative assessment of effectiveness is intended to help prioritise the most suitable measures in view of limited financial and human resources.
Keywords: 330; design of cultivated landscapes; agriculture; forestry; integrated measures; prioritisation; climate change; climate adaptation; security of food; water and biomass supply; biodiversity